Percutaneous thermal ablation versus open liver resection for recurrent hepatoblastoma: a retrospective study - Si-tong Chen (International Journal of Hyperthermia, 2021)
Background The survival of children with recurrent hepatoblastoma (RHB) is still unsatisfactory and the treatment for relapsed patients is challenging. Purpose To compare short-term results between open liver resection (OLR) and percutaneous thermal ablation (TA) in the treatment of RHB and provide evidence to support the treatment options for such patients. Methods A retrospective data of 21 patients with RHB in two Chinese centers were analyzed from January 2013 to May 2019. The baseline indicators and clinical effect of the two groups of children were compared. Results There was no statistical difference in baseline indicators between the two groups of children, and complete remission (CR) was achieved after comprehensive treatment. The median follow-up time was 30 months (IQR 38.5 months) in the TA group, and 23 months (IQR 21.7 months) in OLR group (p = .57). The 2-year OS rates were 92.3% in the percutaneous TA group and 87.5% in the OLR group (p = .68, HR = 1.6, 95% confidence interval [CI]: 0.2–12.4). The 2-year EFS rates were 66.7%, in the TA group and 50.0% in the OLR group (p = .51, HR = 0.6, 95% CI: 0.2–2.6). Compared with the OLR group, TA group had shorter operation time (3.5 ± 1.8 vs. 0.5 ± 0.1, p < .001) and postoperative hospitalization time (11.8 ± 3.0 vs. 9.5 ± 6.8 d, p = .045). No major complications occurred in both groups. Conclusions Ultrasound-guided percutaneous TA for RHB is a safe and effect treatment option for children. It has comparable effect with surgery within 2 years after treatment. Particularly, due to its minimally invasive advantage, it needs shorter operation and hospitalization time. Percutaneous ablation may be an alternative minimally invasive treatment for RHB children.